Kualitas semen sapi pejantan berdasarkan umur, suhu, dan kelembaban di Taman Ternak Pendidikan Universitas Airlangga - Brillianti, Febby Fairy; Srianto, Pudji; Sardjito, Trilas; Suprayogi, Tri Wahyu; Triana, Indah Norma; Rahardjo, Dadik (Universitas Airlangga, 2021)
This research was conducted in the teaching farm of the Faculty of Veterinary Medicine, Universitas Airlangga. The present study aimed to determine the effect of age, temperature, and humidity on bull semen quality which was processed into frozen semen. Three age groups of bulls (young 3-4 years, middle age 5-6 years, and old 7-8 years) were collected for the temperature and humidity of semen examination. Fresh semen was collected using an artificial vagina, followed by macroscopic and microscopic examination. In addition, post-thawing motility was also evaluated. The results showed that there was no effect of temperature and humidity during semen collection process. Fresh semen quality was affected by age. Moreover, the post-thawing motility of fresh semen of spermatozoa was lower than those of the fresh semen; however, it still qualifies for artificial insemination. It could be concluded that the semen of bulls at the Teaching Farm of Universitas Airlangga has good quality, and is suitable for Artificial Insemination.